HOAI 2013 : honorarordnung für architekten und ingenieure vom 10. Juli 2013 = HOAI 2013 : official scale of fees for services by architects and engineers dated July 10, 2013.: honorarordnung für architekten und ingenieure vom 10. Juli 2013 = HOAI 2013 : official scale of fees for services by architects and engineers dated July 10, 2013. (2019) - Unknown
No abstract available